Pentingnya Etika Komunikasi Dalam Memperkuat Organisasi Tinjauan Agama Islam - Bagaz Eka Nurdiansyah; Adam Maulana Syahadji; Ismail Mubarok (Pusat Riset dan Inovasi Nasional, 2024)
Islamic communication styles outline a number of principles that teach us how to communicate with other people.This hinders the use of appropriate language, which is clear, concise, and respectful of others.In Islam, true communication is based on the concept of